2014
DOI: 10.1016/j.ajo.2014.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Brimonidine on Retinal Vascular Autoregulation and Short-term Visual Function in Normal Tension Glaucoma

Abstract: Brimonidine significantly improved impaired retinal vascular autoregulation in normal tension glaucoma patients, but short-term alteration in visual function could not be demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 34 publications
0
29
1
2
Order By: Relevance
“…; Feke et al. ). In addition, increased retinal susceptibility to glaucomatous damage with diabetes‐related vascular changes may also explain the association (Kanamori et al.…”
Section: Discussionmentioning
confidence: 97%
“…; Feke et al. ). In addition, increased retinal susceptibility to glaucomatous damage with diabetes‐related vascular changes may also explain the association (Kanamori et al.…”
Section: Discussionmentioning
confidence: 97%
“…Although both groups had similar flow values at baseline, the glaucomatous cohort showed a broad and significant range of hemodynamic responses while lying flat compared with sitting (p = 0.0025), indicating vascular dysregulation. Subsequent work by the same group evaluated the effect of glaucoma medications on retinal autoregulation using the same methodology and found that brimonidine significantly improves retinal vascular autoregulation in NTG patients [150,151] and that switching from timolol to dorzolamide/timolol improves autoregulation in OAG patients significantly, whereas brimonidine/timolol does not [152].…”
Section: Refmentioning
confidence: 96%
“…2 Moreover, brimonidine tartrate ophthalmic solution 0.15% significantly improves retinal vascular autoregulation in normal-tension glaucoma patients. 8 To confirm whether the concentration of brimonidine in the vitreous is enough to exhibit neuroprotection in the retina, quantitative measurement of the drug in ocular media has been carried out after the topical administration of brimonidine tartrate 0.2% and 0.15%. 9,10 Most of the brimonidine tartrate-administered eyes showed the concentration of more than 2 nM in the vitreous, which is known to activate neuroprotective a-2 receptors in animal retina.…”
Section: Introductionmentioning
confidence: 99%